Unfractionated heparin in ruptured aortic aneurysms – narrative review - Ribeiro, Tiago F. (2024)
INTRODUCTION: Portuguese estimates point out that nearly 20% of aortic aneurysms are treated in a ruptured setting, with in-hospital mortality reaching up to 50%. Although unfractionated heparin (UFH) is routine during elective surgery, this technical point is debatable when treating ruptured aneurysms. The authors aimed to review the literature on the topic of intraoperative heparinization with UFH within the intraoperative period of ruptured aortic aneurysms. METHODS: A MEDLINE and Scopus database search using the terms “unfractionated heparin," “aortic aneurysm," and “ruptured aortic aneurysm” was performed. No time or language limitations were imposed. The last search was run in July 2023. Manuscripts were considered irrespective of study design. Additional articles of scientific interest for the purpose of this non-systematic review were included by cross-referencing. RESULTS: In the rupture setting, UFH usage rates have widely varied throughout time and geographical sites, and they are reported to be as low as 16%. Overall, the evidence of UFH in clinical practice in this scenario is limited. Notwithstanding, there is some evidence from observational studies of an increased pro-coagulant activity in this clinical scenario, favoring a theoretical physiologic benefit. A prospective, non-randomized study of 131 OSR patients found that patients treated with UFH had improved 30-day survival (84% vs 67%, P=0.001). Non-significant differences in blood product usage were noted. Therefore, societal guideline recommendations about intraoperative UFH in ruptured aortic aneurysms are often missing. CONCLUSION: UFH may potentially reduce death after open repair of rAAA. These findings should be carefully interpreted, as the evidence is scarce and heterogeneous and only portrays open repair.